# Class 11 RD Sharma Solutions – Chapter 14 Quadratic Equations – Exercise 14.1 | Set 1

• Last Updated : 21 Dec, 2020

### Question 1.x2 + 1 = 0

Solution:

We can write the given equation as,

Hey! Looking for some great resources suitable for young ones? You've come to the right place. Check out our self-paced courses designed for students of grades I-XII

Start with topics like Python, HTML, ML, and learn to make some games and apps all with the help of our expertly designed content! So students worry no more, because GeeksforGeeks School is now here!

x2 – i2 =0, where i = iota = √(-1)

Now factorizing above equation,

(x + i)(x – i) = 0

So, x + i = 0 and x – i = 0

x = -i and x = +i

Hence, roots will be +i and -i.

### Question 2. 9x2 + 4 = 0

Solution:

We can write the given equation as,

9x2 – 4(i2) = 0

(3x)2 – (2i)2 = 0

(3x – 2i)(3x + 2i) = 0

So, 3x – 2i = 0 and 3x + 2i = 0

x = 2i/3 and x = -2i/3

Hence, roots will be 2i/3 and -2i/3.

### Question 3. x2 + 2x + 5 = 0

Solution:

We can write the given equation as,

(x2 + 2x + 1) + 4 = 0

(x2 + 2x + 1) – 4(i2) = 0

(x + 1)2 – (2i)2 = 0

(x + 1 – 2i)(x + 1 – 2i) = 0

So, (x + 1 – 2i) = 0 and (x + 1 – 2i) = 0

x = -1 + 2i and x = -1 – 2i

Hence, roots will be -1 + 2i and -1 – 2i.

### Question 4. 4x2 – 12x + 25 = 0

Solution:

We can write the above equation as,

4x2-12x+9+16=0

(4x2 -12x +9) – 16(i2)=0

(2x-3)2 – (4i)2=0

(2x-3+4i)(2x-3-4i)=0

So, (2x-3+4i)=0 and (2x-3-4i)=0

x=(3-4i)/2 and x=(3+4i)/2

Hence, roots will be (3/2-2i) and (3/2+2i).

### Question 5. x2 + x + 1 = 0

Solution:

We can write the above equation as,

x2+x+(1/4)+(3/4)=0

(x+1/2)2  – (3/4)(i2)=0

(x+1/2)2 – ((√3)/2 i)2=0

(x+1/2+ (√3)/2 i)(x+1/2-(√3)/2 i)=0

So, (x+1/2+ (√3)/2 i)=0 and (x+1/2-(√3)/2 i)=0

x=(-1-(√3)i)/2 and x=(-1+(√3)i)/2

Hence, roots will be x=(-1-(√3))/2 i and x=(-1+(√3))/2

### Question 6. 4x2 + 1 = 0

Solution:

We can write the above equation as,

4x2-1(i2) = 0

(2x)2-(i) 2=0

(2x-i)(2x+i)=0

So, (2x-i)=0 and (2x+i)=0

x=i/2 and x= -i/2

Hence, roots will be x=-i/2 and x=i/2.

### Question 7. x2 – 4x + 7 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=1,b=-4,c=7

Using Discriminant Method,

D= (b2-4ac)

D= ((-4)2 – 4*1*7)

D= (16 -28)

√D= √(-12)= 2√3 i

So, roots will be

R1= (-(-4) + 2√3 i)/2 and R2= (-(-4) – 2√3 i)/2

R1= 2+√3 i and R2= 2-√3i

### Question 8. x2 + 2x + 2 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=1,b=2,c=2

Using Discriminant Method,

D= (b2-4ac)

D= ((2)2 – 4*1*2)

D= (4 – 8)

√D = √(-4)

√D= 2i

So, roots will be,

R1= (-(2) + (2i))/2 and R2 = (-(2) – (2i) )/2

Hence, R1= -1+i and R2=-1-i.

### Question 9. 5x2 – 6x + 2 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=5,b=-6,c=2

Using Discriminant Method,

D = (b2-4ac)

D = ((-6)2 – 4*5*2)

D  = (36- 40)

√D = √(-4)

√D = 2i

So, roots will be,

R1= (-(-6) + (2i))/(2*5) and  R2= (-(-6) – (2i) )/(2*5)

Hence, R1= (3+i)/5 and R2=(3-i)/5.

### Question 10. 21x2 + 9x + 1 = 0

Solution:

Comparing the equation with ,

ax2+bx+c=0

We get, a=21,b=9,c=1

Using Discriminant Method,

D= (b2-4ac)

D= ((9)2– 4*21*1)

D= (81- 84)

√D= √(-3)

√D=√3 i

So, roots will be,

R1= (-(9)+ √3 i)/(2*21) and  R2= (-(9) – √3 i)/(2*21)

Hence, R1= -3/14+√3i/42 and R2= -3/14-√3i/42.

### Question 11. x2 – x + 1 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=1,b=-1,c=1

Using Discriminant Method,

D= (b2-4ac)

D= ((-1)2– 4*1*1)

D= (1- 4)

√D= √(-3)

√D=√3 i

So, roots will be,

R1= (-(-1)+ √3 i)/2 and R2= (-(-1) – √3 i)/2

Hence, R1= (1+√3i)/2 and R2= (1-√3i)/2.

### Question 12. x2 + x + 1 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=1,b=1,c=1

Using Discriminant Method,

D= (b2-4ac)

D= ((-1)2– 4*1*1)

D= (1- 4)

√D= √(-3)

√D=√3 i

So, roots will be,

R1= (-(1)+ √3 i)/2 and R2 = (-(1) – √3 i)/2

Hence, R1= (-1+√3i)/2 and R2= (-1-√3i)/2.

### Question 13. 17x2 – 8x + 1 = 0

Solution:

Comparing the equation with,

ax2+bx+c=0

We get, a=17,b=-8,c=1

Using Discriminant Method,

D= (b2-4ac)

D= ((-8)2– 4*17*1)

D= (64- 68)

√D= √(-4)

√D=2i

So, roots will be,

R1= (-(-8)+ 2i)/(2*17) and  R2= (-(-8) – 2i)/(2*17)

Hence, R1= (4+i)/17 and R2= (4-i)/17.

My Personal Notes arrow_drop_up